Fast-track surgery for colonic and rectal resections in Austria: results from a survey on the perioperative anaesthesia management = "Fast-Track"-Chirurgie im Rahmen kolorektaler Resektionen in Österreich : Umfrage zum perioperativen anästhesiologischen Management - Hasenberg, Till; Reibenwein, B.; Längle, F.; Schindler, K.; Post, Stefan; Spies, C.; Schwenk, W.; Shang, Edward (European surgery, 2010)
BACKGROUND: "Fast-track" rehabilitation can accelerate recovery, reduce general morbidity and decrease hospital stay after elective colorectal surgery. Despite this evidence, there is no information on the acceptance and utilization of these concepts amongst Austrian anaesthesiologist. In addition to that differences between colonic and rectal resections have not been addressed yet. METHODS: A questionnaire concerning perioperative routines in elective, open colonic and rectal resection was sent to the senior anaesthesiologist in 120 Austrian digestive surgical centres. RESULTS: The response rate was 63% (76 centres). Prophylactic measures for postoperative nausea and vomiting (PONV) were administered in 32% of clinics. Epidural analgesia is in use in three-quarters both of the institutions, regardless of the procedure. Short-acting anaesthetics were used for colonic as well as rectal resections. Normothermia is provided by the majority of anaesthetists. CONCLUSIONS: In Austria the anaesthesiological routine after elective colonic and rectal surgery adheres broadly to the evidence-based recommendations for fast-track concepts.